PENERAPAN MODEL PROBLEM POSING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPA KELAS V SDN DUREN SAWIT 13 - Devinna Andarini Saputri; Endang Wahyudiana; Anggi Citra Apriliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the critical thinking skills of fifth grade students of SDN Duren Sawit 13 through the application of the Problem Posing learning model. The method used is Classroom Action Research (CAR) with the Kemmis and McTaggart model. Each cycle includes the planning, action, observation, and reflection stages. The results of the study showed that in cycle I, students' critical thinking skills that achieved a score of ≥70 were 72%, with teacher actions of 85% and student activities of 80%. After improvements in cycle II, there was a significant increase, namely 88% of students achieved a score of ≥70, while teacher actions and student activities reached 100%. This increase shows that the Problem Posing model is effective in developing students' critical thinking skills. This model encourages students to actively formulate questions, solve problems, and understand the material in depth. Thus, the Problem Posing model can be used as a relevant learning strategy in the Merdeka curriculum to improve the quality of science learning and critical thinking skills of elementary school students. This study recommends the application of this model more widely to create active, contextual, and meaningful learning.